Confronting Complex Accountability in Conservation With Communities - Crosman, Katherine M.; Singh, Gerald G.; Lang, Sabine (Frontiers in Marine Science, 2021)
Increasingly, conservation organizations are conducting conservation activities with local communities. Many conservation organizations now position their work as contributing to sustainable development initiatives, and local involvement in conservation is understood to increase conservation and sustainability success. Aside from communities, however, conservation organizations are accountable to funders and partners, and values and priorities vary across actor type. Mismatched goals combine with power imbalances between conservation actors, and create decision-making conflict throughout conservation processes, from objective setting through implementation and evaluation. As a result, communities may lose local decision-making power or face new negative consequences, trust in organizational/community partnerships may be undermined, and conservation organizations’ reputations (and the reputation of the sector as whole) may suffer. In this commentary we point out processes and conditions that can lead conservation organizations to privilege accountability to funders and others over accountability to communities, thereby undermining community-level success. We follow with suggestions for how funders, conservation organizations and others may improve community engagement and community-level outcomes, and improve their reputations in general and in their work with communities, by actively leveraging accountability to the community and involving local community members in decision-making.